The renewal of post-war Manchester - Brook, Richard (Manchester University Press, 2025)
This book is about an exciting time in the development of European cities – from the 1950s to the 1970s – when capital flowed, energy was cheap and abundant, citizens were more mobile than ever before, and a new optimism was embodied in popular culture. The experiences of the Second World War provided the spatial, technological and governmental foundations for the modernisation of Britain. New technologies were born of war and regional political structures were also a product of conflict. Certain British cities were the testing ground for new ideas in planning and architecture, amidst new statutory contexts and a raft of policy implemented to order the built environment. This title focuses acutely on these networks and tracks the relationships between central and local government and their influence on buildings, public space and infrastructure. It uses the planning and architecture of Manchester as a case through which to reveal shifts in politics, economics and culture in the post-war period. It is part urban history, part planning history and part architectural history. For the first time, it uncovers the complex forces acting upon the production of space in the renewal cities of the 1960s and the close and direct relations between state legislation, planning policy definition and architectural production. Backgrounded by the global meta-narratives of the Cold War, decolonisation and the rise of consumer capitalism, the major empirical chapters show how international forces also impacted and influenced the development of cities.